Conceptual Framework for The Idea of Criminal Logic - Majid khdr Ahmad al- sabawi; Mustafa Ismael Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The emergence of the term legal logic was in (1615 AD) in Latin (LOGICA JURIDICA) and a large group of jurists, philosophers and thinkers were interested in this term to explain and root it to benefit from the science of logic in the field of law and the field of justice. Legal logic is the logic that is concerned with the study and analysis of intellectual processes related to law that focus on legal concepts and terms. Legal is the law in general without any specification and specification, and legal logic studies the mental foundations of the law in terms of its genesis, formation, development and application. The side of the accused, and he uses it to bring down the rule of law on her, and the judge is obliged in the form of following the methods of logical reasoning, and it can be said that the judicial criminal logic is a part of the legal logic in general, because the judicial logic is originally the practical part of the legal logic, and the judicial criminal logic can be defined, It is the logic used by the criminal judge in forming his conviction with the evidence and supporting it, and then in issuing his penal judgment. As for criminal logic in its special sense, it is the type of logic found in both legal logic and judicial logic, and that criminal logic has a connection and interrelationship with legal logic in the enactment of laws by the legislator. Judicial logic also, because the judge uses criminal logic to interpret and analyze texts until the stage of supporting evidence and then the stage of issuing a judgment.